Clinical Research before Informed Consent - Miller, Franklin G. (Kennedy Institute of Ethics journal, 2014)
Clinical research with patient–subjects was routinely conducted without informed consent for research participation prior to 1966. The aim of this article is to illuminate the moral climate of clinical research at this time, with particular attention to placebo-controlled trials in which patient–subjects often were not informed that they were participating in research or that they might receive a placebo intervention rather than standard medical treatment or an experimental treatment for their condition. An especially valuable window into the thinking of clinical investigators about their relationship with patient–subjects in the era before informed consent is afforded by reflection on two articles published by psychiatric researchers in 1966 and 1967, at the point of transition between clinical research conducted under the guise of medical care and clinical research based on consent following an invitation to participate and disclosure of material information about the study. Historical inquiry relating to the practice of clinical research without informed consent helps to put into perspective the moral progress associated with soliciting consent following disclosure of pertinent information; it also helps to shed light on an important issue in contemporary research ethics: the conditions under which it is ethical to conduct clinical research without informed consent.